EXPLORING STUDENTS’ PERCEPTION AND MOTIVATION TOWARD ENGLISH E-LEARNING DURING THE COVID-19 PANDEMIC - Fernanda, Novela (ELP (Journal of English Language Pedagogy), 2023)
The purpose of this study was to investigate students' perceptions and motivations toward English e-learning during the Covid-19 pandemic in the school year 2021/2022. The research was conducted using a descriptive quantitative method and involved a sample of nineteen students from grade VIII of SMPN 7 Gunung Talang. The data was collected using a questionnaire designed by the researcher. The questionnaire provided students with a response column to indicate their choices. In the study, 56 perception statements with three aspects and 26 motivation statements with two aspects were used. The results of the study showed that the perception of English e-learning was positive and received a perception score of 49%, and the motivation towards e-learning was rated at 41%. Both perception and motivation were rated as good. The study concluded that English e-learning was effective and appropriate during the COVID-19 pandemic. The study recommends that English teachers adopt creative approaches to effectively educate students and increase motivation for e-learning in possible future situations similar to the COVID-19 pandemic.